Perilaku Kekerasaan Dalam Rumah Tangga Sebagai Pelanggaran Hak Asasi Manusia - Ahmad Mukri Aji (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:Domestic violence is a behavior that can be categorized as a violation of human rights. Because this behavior results in disruption of the social dimension of humanity, due to actions that do not humanize humans in general. Even in the context of domestic violence, the perpetrators who are supposed to protect even commit acts of violence, mistreatment, intimidation and even the loss of the victim's life. The research method uses the normative juridical method, using secondary data obtained through literature study and analyzed qualitatively. The results and discussion of this study are that there are aspects of human rights violations that occur in domestic violence behavior. So the government is obliged to take action in the form of legal protection for victims by ensnaring the perpetrators with laws and regulations. Both the Criminal Code and the Law on the Elimination of Domestic Violence.Keywords: Domestic Violence Behavior, Human Rights, Violence.